Novel implementation research designs for scaling up global mental health care: overcoming translational challenges to address the world's leading cause of disability. Issue 1 (December 2016) - Meffert, Susan; Neylan, Thomas; Chambers, David; Verdeli, Helen
Abstract Despite established knowledge that Low and Middle Income Countries (LMICs) bear the majority of the world's burden of mental disorders, and more than a decade of efficacy research showing that the most common disorders, such as depression and anxiety, can be treated using readily available local personnel in LMICs to apply evidence-based treatments, there remains a massive mental health treatment gap, such that 75 % of those in LMICs never receive care. Here, we discuss the use of a new type of implementation science study design, the effectiveness-implementation hybrids, to speed the translation and scale up of mental health care in LMICs. We use our current study of Interpersonal Psychotherapy (IPT) delivered by local personnel for depression and trauma-related disorders among HIV+ women in Kenya as an example of effectiveness-implementation hybrid design for mental health services research in LMICs.